Competitiveness of the Human Capital as Strategic Resource of Innovational Economy Functioning - CHERKESOVA, Elvira Y.; BREUSOVA, Evgeniya A.; SAVCHISHKINA, Ekaterina P.; DEMIDOVA, Nataliya E. (Journal of Advanced Research in Law and Economics, 2017)
The article covers the problem related to forming the human capital as a strategic resource of innovational economy functioning. It considers and analyzes the framework of categories used when studying theoretic and practical aspects of forming the human capital and competitiveness of the human capital, and researches various positions of national and foreign researchers on the essence of key notions and factors that influence the formation of the human capital. The reasonability of investments in the human capital in the long-term perspective is stipulated. The article specifies that the creation and efficient use of the human capital as a strategic resource of the company leads to actual competitive advantages of the company on the market. The author defines that the tools to form the competitive human capital as a strategic resource of the innovational economy functioning include the optimization of budgetary expenses and rational investment of resources in education and science.